Strength Analysis on Yoke Single Point Mooring with Finite Element Method - Dianiswara, Anggoronadhi; Rahmatikah, Maya; Huda, Abiyani Choirul (Naval Architecture Department, Kalimantan Institut of Technology, 2023)
Analysis of stresses and deformations in the Single Point Mooring (SPM) yoke structure using the Finite Element Method (FEM) aims to determine and understand the stress distribution and deformation of the yoke, so that offloading activities comply with safety standards. The finite element method is a numerical modeling technique used to predict the behavior of a system by dividing an object into a number of elements that can be analyzed independently. This study uses 3 geometric models, namely single point mooring yoke geometry aged 0, 20, and 30 years. The results of the analysis will assist in understanding the stresses and deformations that occur in the SPM yoke structure. To simulate the tension of the ship during unloading, tensions of 75, 100, and 125 tons are represented. For each geometry, the greatest stress and deformation values found are 89 MPa for the 0-year model, 89.2 MPa for the 20-year model, 97.1 MPa for the 30-year model, respectively, and 0.08 mm for the 0-year model, 0.10 mm for the 20-year model, 0.11 mm for the 30-year model. This investigation demonstrates that the observed stress levels and deformations comply with safety standards.